Moving Beyond the Law of The Fathers Toni Morrison's Paradise - M. M. Slaughter (Law Text Culture, 2000)
You don't have to know the work of the legal theorist, Pierre Legendre, to read Toni Morrison's new novel, Paradise (Morrison 1997) but it doesn't hurt. The novel is not ostensibly about law (as one might expect, in Paradise there is no crime). Nevertheless, law is central to the novel. It is what the paradisal community rests on, the foundation of the symbolic order. It lays down what would be taken to be the inalterable places of this society and culture. Law is constitutive, what constitutes, constitutional; which as we shall see is no fortuitous analogy. Paradise is a story of foundations, or foundational myths, at the center of which is law. With unusual uncanniness, these not-so-buried themes in Morrison's work overlap with Legendre's psychoanalytically based legal theories. If his work is an explication and explanation of the symbolic function of law -- what rests in society's legal unconscious -- Morrison's novel is an illustration of it. While the point of this paper is not to illustrate Legendre but to illuminate Morrison, awareness of Legendre makes corners and connections in Paradise brighter.